Comparative study on membrane distillation application between raw POME and POMSE - Nadzirah, Mohd Mokhtar; N. A.S., Muhamad; Lau, W. J.; Ismail Fauzi, A.F.; Rosmawati, Naim (Elsevier Ltd, 2023)
The palm oil industry is considered the traditional pillar of Malaysian industry that plays a key role in the domestic economy. In addition to the high incomes generated by this industry, it generates large quantities of effluent. To solve this problem, the purpose of this work is to introduce membrane distillation (MD) technology for the effluent treatment system. Polyvinylidene fluoride (PVDF) -bentonite hollow fiber membranes were tested in an MD system using raw palm oil mill effluent (POME) and palm oil mill secondary effluent (POMSE). Preliminary test was carried out using deionized water to evaluate the maximum permeate flux achievable in the absence of fouling problem before continuing with POME and POMSE as the feed solution. Membrane performance was evaluated in terms of permeate flux and rejection rate of several water quality parameters. The average permeate flux obtained while using raw POME is much lower than that obtained in the POMSE test which was recorded as 1.41 ± 0.62 kg/m2.hr and 3.45 ± 0.51 kg/m2.hr respectively. The membrane tested for POME experienced a significant decrease in flux relative to POMSE due to the excessive amounts of biological compounds blocking the membrane pores. In terms of removal efficiency of the PVDF-bentonite membrane, the membranes were able to achieve more than 95% removal efficiency for chemical oxygen demand, nitrate nitrogen, total suspended solids, total dissolved solids, color and turbidity. The results proved that the DCMD system was able to eliminate almost all pollutants in the effluent from oil palm industry. However, raw POME without pre-treatment is not suitable to be used directly in the DCMD process because it will cause a serious fouling problem. In conclusion, it can be said that MD has shown excellent performance in the treatment of palm oil wastewater and can be applied to other types of oil industries.